Persepsi Dan Dinamika Kelompok Pengrajin Dalam Pengembangan Usaha Agroindustri Berbasis Nenas Di Desa Kualu Nenas Kecamatan Tambang Kabupaten Kampar - Yulida, Roza; ', Nurazmi; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The successful of pineapple based agro-industry business is influenced by the perception and the group dynamics of the agro-industry enterprises. This study aimed to determine the perceptions and dynamics of craftsmen group and also to determine pineapple based agro-industry business development for individual and group in Kualu Nenas Village Tambang District of Kampar Regency Riau Province. This research was conducted on October 2012 to September 2013 by using saturated sampling (census) and a sample of 11 pineapple chips of craftsmen.The results showed that the craftsman perception of effort is good enough, with a score of 3.39. Group dynamism as measured from 9 variables with a score of 2.27 which states that the craftsmen group are not dynamic. Development of pineapple based agro-industry business when viewed from an individual business is pretty good enough with a score of 3.02. On the other hand, when viewed as a group of businesses, such efforts have not been further developed as indicated by a score of 1.80. Keywords: Perception, dynamics of group, agro-industry, pineapple